Bipartisan Drug-Patent Bills Ready for Senate Vote: Efforts Directed at Speeding Up Introduction of Generics - Barlas, Stephen (P T, 2019)
The legal tactics that drug manufacturers use to extend drug patents may be the biggest impediment to lowering drug prices and to Congress acting on pricing. Until now, that is.